2020
DOI: 10.1089/vbz.2019.2518
|View full text |Cite
|
Sign up to set email alerts
|

Development of a PCR Kit for Detection of Coxiella burnetii in Ukraine

Abstract: Coxiella burnetii is an obligate intracellular pathogen and the causative agent of Q fever. In Ukraine, 28 human cases of Q fever were reported between 1997 and 2006; however, there are no state-approved, standardized molecular diagnostic assays that can be used systematically to investigate C. burnetii transmission to humans and its distribution throughout Ukraine. To address this deficiency, we followed the recommendation of the World Organization for Animal Health (OIE) and developed a confirmatory PCR for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Astobiza et al (2012) detected that serological results should be further analyzed with caution, and that other complementary analysis needed to be done (32). Therefore, our results were in expectance since PCR was more sensitive and greatly specific than ELISA in detecting of C. burnetii (33,34). There was a high possibility of false positive or negative ELISA can be resulted due to insufficient blocking of immobilized antigen, antibody instability, seroconversion, and crossreaction of the secondary antibody (35).…”
Section: Discussionmentioning
confidence: 78%
“…Astobiza et al (2012) detected that serological results should be further analyzed with caution, and that other complementary analysis needed to be done (32). Therefore, our results were in expectance since PCR was more sensitive and greatly specific than ELISA in detecting of C. burnetii (33,34). There was a high possibility of false positive or negative ELISA can be resulted due to insufficient blocking of immobilized antigen, antibody instability, seroconversion, and crossreaction of the secondary antibody (35).…”
Section: Discussionmentioning
confidence: 78%
“…In addition, there is a potential risk of infection in humans through a variety of ways. Individuals involved in animal farming are particularly at risk (20,24). The results of this study indicated the prevalence of C. burnetii in cow and buffalo milk samples in the Urmia region.…”
Section: Discussionmentioning
confidence: 58%
“…It is a sensitive, safe, and specific procedure to detect C. burnetii in various specimens (19). Various target genes were used (20) for specific C. burnetii identification, such as com1 encoding a 27 kDa outer membrane protein, the superoxide dismutase (Sod B) gene, and the heat shock operon that encodes 2 heat shock proteins (htpA and htpB). The other target genes include the macrophage infectivity potentiator protein (cbmip), isocitrate dehydrogenase (icd), and a transposon-like repetitive region of the C. burnetii genome.…”
mentioning
confidence: 99%
“…Polymerase chain reaction (PCR) is one of the impor-tant detection methods to detect various pathogens like SARS CoV-2. Influenza virus, Hepatitis C virus, Coxiella burnetii and many other pathogens [1][2][3][4][5][6][7][8][9]. Moreover there are large number of RNA viruses in ticks, which are needed to be addressed [10].…”
mentioning
confidence: 99%